Chest Tube Insertion Following a Failed Needle Decompression in a Patient with Tension Pneumothorax: a Case ReportChest tube insertion following a failed needle decompression in a patient with tension pneumothorax: A case report - Saleh, Nanang Salman; Wisnu, Gusti Ngurah P Pradnya; Muhaimin, Alim; Sugianto, Dea Tasha Meicita Kis (Universitas Muhammadiyah Surabaya, 2024)
Pneumothorax occurs when the pleural space is filled with air due to trauma, iatrogenic injury, or underlying lung disease. If this air leak forms a one-way valve that causes air to be trapped, an uncontrolled increase in air volume can occur, causing lung collapse and shift of the mediastinum to the contralateral side, which can eventually cause respiratory and hemodynamic disturbances or even death. Here, we report a 46-year-old male patient who came to the hospital complaining of shortness of breath and chest pain radiating to the left shoulder. On physical examination, the patient had severe shortness of breath, tracheal deviation, decreased expansion and air entry of the left hemithorax, hyperresonance of the left hemithorax, and a shift of the punctum maximum of the heart sounds to the left sternal line. The chest x-ray performed on the patient confirmed the suspicion of a tension pneumothorax. A needle decompression in the 2nd intercostal space in the left midclavicular line failed to improve the tension pneumothorax. A chest tube insertion was performed which managed to improve the patient's clinical condition.